The role of convenience in a recreational shopping trip. Issue 11 (4th November 2014) - Reimers, Vaughan; Chao, Fred
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to determine the role of convenience in a recreational shopping trip. In an effort to address the shopping strip's forfeiture of market share to the mall and the Internet, retail planners have utilised a variety of intervention strategies. One such strategy is to differentiate the strip by emphasising its hedonic attributes. An often overlooked alternative is to compete with both of these formats in a key area of competitive disadvantage – convenience. Whereas these two alternatives have traditionally been regarded as separate strategies, this study examines whether convenience actually serves as a source of satisfaction in a hedonic shopping context. Design/methodology/approach – A recreational shopping trip to a shopping strip (also referred to as Main Street or the High Street) in Melbourne, Australia, served as the context for this study. The study used a quantitative survey approach to collect its data and structural equation modelling to analyse it. Findings – Surprisingly, the hedonic attributes of a shopping strip do not influence trip satisfaction in the context of a recreational shopping strip. Contrary to a significant body of academic research, it is instead the time-saving and distance-minimising properties of a shopping strip, as well as its overall convenience, which determine satisfaction. Originality/value – The results have important implications for Town Centre Management schemes because they suggest that responsibility for providing a hedonic shopping experience rests with its individual retailers. Instead, the role of strip planners is to facilitate the other side of the value-equation by minimising the hassles involved in strip shopping. The results of this study also question the traditional belief that hedonic- and convenience-based rejuvenation strategies should be treated as two distinct strategies. Instead, convenience should be regarded as a prerequisite to a satisfying recreational shopping trip.